Pendekatan Motivasi Intrinsik dan Ekstrinsik dalam Mengukur Penggunaan Layanan Mobile Payment (Studi Kasus Pada Pengguna LinkAja di Kota Denpasar) - Permana, Gusi Putu Lestara; Hiu, Victor; Paramartha, I Gusti Ngurah Darma (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2021)
Abstract - The purpose of this study was to measure the interest in using LinkAja m-payment services in Denpasar and measured by adopting a modified and adapted technology acceptance model or TAM theory by adding extrinsic motivation, namely perceived enjoyment. This study took a population of all LinkAJa mobile payment users in the city of Denpasar, which then reduced the entire population using incidental sampling and obtained a research sample of 95 samples whose data were collected using a questionnaire, then the data that had been obtained were analyzed by partial least. square through SmartPLS 3. After analyzing this research, it manifests that the addition of intrinsic and extrinsic constructs is able to predict the interest in using the LinkAja mobile payment application in Denpasar City.